Honey with Coffee: A new finding in the treatment of Persistent Postinfectious Cough - Mohammad-Ali Raeessi; Jafar Aslani; Homa Gharaie; Ali-Akbar Karimi Zarchi; Neda Raeessi; Shervin Assari (Iranian Journal of Otorhinolaryngology, 2011)
Introduction: Persistent postinfectious cough (PPC) is a cough that persists longer than 3 weeks or perhaps for many months after a common cold or an upper respiratory tract infection (URTI). PPC has poor response to routine treatment modalities, so it can be a vexing problem for the patient and the physician alike. Our hypothesis was that honey and/or coffee have some beneficial effects in the treatment of PPC. The aim of this study was to evaluate the therapeutic effects of coffee and/or honey in the treatment of patients with PPC. Materials and Methods: This was a double blind randomized clinical trial, conducted on adult patients during a 6-year period from 2003 to 2009. Included in this study were 84 adult participants that had experienced PPC longer than 3 weeks. All of them had the history of several referrals to different physicians and despite treatment, their cough had persisted. Patients with other causes of chronic cough, or systemic disease or with abnormal routine laboratory tests were excluded. All the included 84 participants were distributed into three groups. For all the participants, a jam-like paste was prepared. Each 600 grams of the product consisted of "70 grams original instant coffee" in the first regimen, "500 grams of honey" in the second regimen and "70 grams of instant coffee plus 500 grams of honey" in the third regimen. These participants were told to dissolve 25 grams of the prescribed product in about 200 CC of warm water (under 60o C), and drink this solution every 8 hours for one week. All the participants were evaluated before and at the end of the first week of their treatment, to measure the frequency of their cough. In addition they were under observation for the first month. Results: Comparing the effectiveness of all three treatment regimens, this study found "honey with coffee" as the most effective treatment modality for PPC (P